Non-contact detection algorithm and realisation of displacement of suspended cylinder. Issue 364 (2nd January 2019) - Xiao, D.; Tan, L.; Su, Y.; Yu, B.; Yang, Y.
Abstract : Large structures such as TV towers and suspension bridges often contain cylindrical components; the displacements of these suspended cylinders due to external agents are often of interest to ensure the integrity of the structure. This paper establishes an algorithm of the displacement monitoring for the suspended cylinder by non-contact surveying, which offers two main advantages over traditional contact-based methods. First, it does not require prisms to be physically mounted on the measuring target and second, the target consists of any three points on the same circle along the structure, which can be easily implemented. The algorithm is successfully applied in determining the displacement of suspended cylinder in high-rise structures such as a TV tower.